The Role of the Currency Board in Bulgaria's Stabilization - Gulde, Anne. (Washington, D.C. : International Monetary Fund, 1999)
This paper focuses on the process leading to the choice of a currency board as a stabilization instrument, and its specific design. The use of a currency board was complicated and controversial because of serious structural problems, including a systemic banking crisis. It argues that the arrangement was well designed for the task at hand, combining a traditional rule-based exchange arrangement with a number of legal and structural measures to address the pressing bank sector and fiscal issues. In light of the interdependence of the measures, the success of Bulgaria's currency board stabilization must be attributed to a combination of elements, of which the currency board was a crucial, but not the only determining factor. Structural problems, most notably in the banking sector, were equally severe. The banking crisis had been smoldering since at least 1995. A 1996 review found that out often state banks, which still accounted for more than 80 percent of banking sector assets, nine had negative capital and more than half of all state banks' portfolios were nonperforming.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet